2018
DOI: 10.1007/s41635-018-0035-4
|View full text |Cite
|
Sign up to set email alerts
|

The Conflicted Usage of RLUTs for Security-Critical Applications on FPGA

Abstract: Modern field programmable gate arrays (FPGAs) have evolved significantly in recent years and have found applications in various fields like cryptography, defense, aerospace, and many more. The integration of FPGA with highly efficient modules like DSP and block RAMs has increased the performance of FPGA significantly. This paper addresses the lesser explored feature of modern FPGA called as reconfigurable LUT (RLUT) whose content can be updated internally, even during runtime. We describe the basic functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Hardware Trojans and side-channel attacks can damage critical operations and cryptographic keys; hence, secure hardware modules like TEEs and enclaves are essential. Critical computations and cryptographic activities are executed securely in the IC architecture using these trusted hardware modules, assuring data confidentiality, integrity, and authenticity (Roy et al, 2018). ICs with physically unclonable functions (PUFs) and true random number generators (TRNGs) improve cryptographic operations and authentication procedures.…”
Section: Integration Of Trusted Hardware Modulesmentioning
confidence: 99%
“…Hardware Trojans and side-channel attacks can damage critical operations and cryptographic keys; hence, secure hardware modules like TEEs and enclaves are essential. Critical computations and cryptographic activities are executed securely in the IC architecture using these trusted hardware modules, assuring data confidentiality, integrity, and authenticity (Roy et al, 2018). ICs with physically unclonable functions (PUFs) and true random number generators (TRNGs) improve cryptographic operations and authentication procedures.…”
Section: Integration Of Trusted Hardware Modulesmentioning
confidence: 99%
“…Log security events and suspected activity for forensic investigation and incident response. Review audit logs and system operations regularly for data breaches and unauthorized reviewed d access (Roy et al, 2018).…”
Section: Secure Data Transmissionmentioning
confidence: 99%
“…Therefore, malicious modifications of the design, referred to as hardware Trojans (HTs), endanger the security of many applications. On FPGAs, a Trojan might be inserted after manufacturing and testing, i.e., in the untrusted field [1], [2], for instance, by altering the entire configuration (known as bitstream) or via partial reconfiguration. Particularly if the chip foundry can be trusted, this depicts a much more powerful threat model than for ASICs.…”
Section: Introductionmentioning
confidence: 99%
“…They show that on an FPGA, longer signal paths can be realized by instantiating route-thru LUTs, or by modifying the routing in the switch boxes, which results in zero overhead in resource usage, and therefore, is hard to detect. In another effort, Roy et al showed that the reconfigurable LUTs could be exploited to realize HTs with zero payload overheads [2]. Finally, Ng et al demonstrated that integrated sensors inside FPGAs could be deployed as Trojan triggers [1].…”
Section: Introductionmentioning
confidence: 99%